The First Case of Usutu Virus Neuroinvasive Disease in Austria, 2021. (16th May 2022) - Graninger, Marianne; Hubmer, Stefan; Riederer, Franz; Kettner, Stephan; Hauk, Martin; Auf, Tasnim; Aberle, Judith H; Stiasny, Karin; Aberle, Stephan W; Camp, Jeremy V
Abstract: Usutu virus (USUV) is a mosquito-borne flavivirus closely related to West Nile virus (WNV) that is endemic in many European countries. We report the first case of USUV neuroinvasive disease in Austria and discuss challenges in differentiating USUV from WNV infections in areas where both viruses are endemic.